ALDEHYDE DEHIDROGENASE LEVEL AND FATTY ACID ETHYL ESTER AS BIOCHEMICAL MARKERS PERSIST LONGER THAN ETHANOL IN WISTAR RATS AFTER CHRONIC ALCOHOL CONSUMPTION - Suaniti, Ni Made; Sudewa Djelantik, A. A. Gde; Suastika, Ketut; Mantik Astawa, Nyoman (Udayana University, 2010)
Alcohol consumption in human has increased from year to year in Indonesia and more recently, anincreasing number of cases of alcohol intoxication, alcoholic liver disease, and death were observed.The purpose of this experimental study was to examine the significance of two known biochemicalmarkers of alcohol given by mouth in the Wistar rats. The study design used was the “Truerandomized experimental post test only control group design